Making Sense of the Unknown: A Narrative Analysis of COVID-19 Stories as Told by WSU Research Students - Alicia Van der Spuy; Lakshmi Jayakrishnan (Research in Social Sciences and Technology, 2021)
Storytelling is an important tool through which to make sense of life experiences. Stories can be classified as personal narratives, historical documentaries and those that inform the viewer about a specific concept or practice. These narratives can be used to promote discussion about current issues in the world. Storytelling can thus be seen as an effective learning tool for students by providing a strong foundation in “Twenty First Century Literacy” skills as well as advancing emotional intelligence and social learning. This project used storytelling to gather information regarding people’s encounters with COVID-19 and lockdown, with specific focus on the Eastern Cape of South Africa. Employing a content analysis methodology, it attempts to analyze responses to narrative inquiry interviews about the COVID-19 pandemic as conducted by students, as part of their introduction to the methodology of research. These responses were used to generalize findings, as well as to look at individual reactions that could bring light to, and make sense of the human experience of the pandemic within an educational context. Both negative and positive experiences were related by interviewees and students.